Interleukin-15 after Near-Infrared Photoimmunotherapy (NIR-PIT) Enhances T Cell Response against Syngeneic Mouse Tumors - Maruoka, Yasuhiro (Cancers (Basel), 2020)
SIMPLE SUMMARY: Near infrared photoimmunotherapy is a newly developed and highly selective cancer treatment that employs a monoclonal antibody conjugated to a photo-absorber dye, IRDye700DX, which is activated by 690 nm light. Cancer cell-targeted near infrared photoimmunotherapy selectively induces rapid necrotic/immunogenic cell death only on target cancer cells and this induces antitumor host immunity including re-priming and proliferation of multi-chronal T-cells that can react with cancer-specific antigens. Interleukin-15 is a type-I cytokine that activates natural killer-, B- and T-cells while having minimal effect on regulatory T-cells that lack the interleukin-15 receptor. Therefore, interleukin-15 administration combined with cancer cell-targeted near infrared photoimmunotherapy could further inhibit tumor growth by increasing antitumor host immunity. In tumor-bearing immunocompetent mice receiving this combination therapy, significant tumor growth inhibition and prolonged survival was demonstrated compared with either single therapy alone, and tumor infiltrating CD8+ T-cells increased in number in combination-treated mice. Interleukin-15 enhances therapeutic effects of cancer-targeted near infrared photoimmunotherapy. ABSTRACT: Near infrared photoimmunotherapy (NIR-PIT) is a newly developed and highly selective cancer treatment that employs a monoclonal antibody (mAb) conjugated to a photo-absorber dye, IRDye700DX, which is activated by 690 nm light. Cancer cell-targeted NIR-PIT induces rapid necrotic/immunogenic cell death (ICD) that induces antitumor host immunity including re-priming and proliferation of T cells. Interleukin-15 (IL-15) is a cytokine that activates natural killer (NK)-, B- and T-cells while having minimal effect on regulatory T cells (Tregs) that lack the IL-15 receptor. Here, we hypothesized that IL-15 administration with cancer cell-targeted NIR-PIT could further inhibit tumor growth by increasing antitumor host immunity. Three syngeneic mouse tumor models, MC38-luc, LL/2, and MOC1, underwent combined CD44-targeted NIR-PIT and short-term IL-15 administration with appropriate controls. Comparing with the single-agent therapy, the combination therapy of IL-15 after NIR-PIT inhibited tumor growth, prolonged survival, and increased tumor infiltrating CD8+ T cells more efficiently in tumor-bearing mice. IL-15 appears to enhance the therapeutic effect of cancer-targeted NIR-PIT.